2019
DOI: 10.1108/ijoa-10-2017-1260
|View full text |Cite
|
Sign up to set email alerts
|

High performance work practices, organizational performance and strategic thinking

Abstract: Purpose Drawing on a number of strategic management theories, the purpose of this paper is to explore the relationship between strategic thinking (in other words, systems perspective, focused intent, intelligent opportunism, thinking in time and hypothesis-driven analysis) and organizational performance. It also investigates whether the notion and content of high performance work practices, as identified in developed countries, can be used to amplify the effects of strategic thinking within the banking industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 113 publications
1
67
0
4
Order By: Relevance
“…Therefore, if the previous experience is positive it will lead the customers to continue with the same provider, however, if it is negative, it will encourage the customers to leave the current service provider. Accordingly, these methods lead the company to know to which extent the customers are satisfied with their service quality (Alatailat et al, 2019;Kuo et al, 2009;Patterson & Spreng, 1997;Taylor & Baker, 1994). The customer normally checks the service and decides whether the quality is consistent with the price (Chen et al, 2008).…”
Section: Service Qualitymentioning
confidence: 99%
“…Therefore, if the previous experience is positive it will lead the customers to continue with the same provider, however, if it is negative, it will encourage the customers to leave the current service provider. Accordingly, these methods lead the company to know to which extent the customers are satisfied with their service quality (Alatailat et al, 2019;Kuo et al, 2009;Patterson & Spreng, 1997;Taylor & Baker, 1994). The customer normally checks the service and decides whether the quality is consistent with the price (Chen et al, 2008).…”
Section: Service Qualitymentioning
confidence: 99%
“…After that the discriminant validity values is assessed using Fornell-Larcker criterion (Fornell & Larcker, 1981;Jahmani et al,2018). The dataset shown discriminant validity is also satisfied if the average variance extracted (AVE) for all constructs is more than 0.50 and the square root of AVE is greater than each correlation coefficient (Alatailat et al, 2019;Alsaad et al, 2017;Becker et al, 2012). See Table 6 below: After examining the measurement model and concluding that validity and reliability values are above the accepted thresholds, the researcher moved forward to examine the structural model.…”
Section: Discussionmentioning
confidence: 99%
“…Fornell and Larcker [5] suggest that that this is not a problem when the composite reliability values are above 0.70, so it can be concluded that the measurement model had adequate convergent validity (see Table 2 ). Table 3 discriminant validity is presented [ 5 , 6 ]; when the values of the square root of AVE are higher than all of the squared values within the correlation matrix, it can be concluded that discriminant validity has been achieved. Comparing the square root of AVE in Table 2 with the values of the squared correlation coefficients in Table 3 , discriminant validity of all constructs in the measurement model is confirmed.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%